Microbiological Quality of Ready-to-Eat Leafy Green Salads during Shelf-Life and Home-Refrigeration - Arienzo, Alyexandra (Foods, 2020)
The market of ready-to-eat leafy green salads is experiencing a noticeable growth in Europe. Since they are intended to be consumed without additional treatments, these ready-to-eat products are associated with a high microbiological risk. The aim of this work was to evaluate the microbiological quality and safety of ready-to-eat leafy green salads sold in widespread supermarket chains in Lazio, Italy, on the packaging date during shelf-life and during home-refrigeration. The study also aimed to determine the differences between low-, medium-, and high-cost products. Salmonella spp. and L. monocytogenes were chosen as safety indicators as specified by European regulations while total aerobic mesophilic bacteria and Escherichia coli were chosen as quality indicators as suggested by national guidelines. Analyses were performed following the ISO standards and in parallel for the evaluation of total aerobic mesophilic bacteria, with an alternative colorimetric system, the Micro Biological Survey method, in order to propose a simple, affordable and accurate alternative for testing the microbiological quality of products, especially suitable for small and medium enterprises and on-site analyses. The study revealed high, unsatisfactory, total bacterial loads in all analyzed samples on the packaging date and expiry date and a very high prevalence of Salmonella spp. (67%) regardless of the selected varieties and cost categories; L. monocytogenes was not recovered aligning with the results obtained in other studies.